How Breathing Exercises Influence on Respiratory Muscles and Quality of Life among Patients with COPD? A Systematic Review and Meta-Analysis - Ruisheng Yun; Yiwen Bai; Yan Lu; Xubo Wu; Shin-Da Lee (Canadian Respiratory Journal)
Aim. This systematic review aimed to investigate the effect of different breathing exercises on respiratory muscle function, 6-minute walk test (6MWT), and quality of life (QoL) in patients with chronic obstructive pulmonary disease (COPD). Methods. We searched online databases including PubMed, Embase, Web of Science, Cochrane Library, and Ovid for randomized controlled trials that assessed the efficacy of breathing exercises on patients with COPD. Patient outcome parameters included changes in respiratory muscle function, 6MWT, and QoL. The Cochrane Collaboration tool was used to assess the risk of bias for each included study. Subgroup analyses concerning different interventions and outcome measurements were conducted as necessary. PROSPERO registration number is CRD42018118367. Results. A total of 17 studies were included for final analysis. Meta-analysis based on the relevant studies showed that breathing exercises had a significant total effect on pulmonary function PImax (mean difference (MD) = 8.65, 95% confidence interval (CI) 3.13–14.16, P=0.002), as well as 6MWT (MD = 27.70, 95% CI 5.45–49.94, P=0.01) in patients with COPD. Conclusions. This systematic review summarized the use of breathing exercises for treating patients with COPD. Breathing exercises were found to be an effective tool for treating patients with COPD by improving inspiratory muscle strength and 6MWT. However, breathing exercises showed no significant improvements on the QoL of patients with COPD.